Pharmacodynamic Evaluation of Zoliflodacin Treatment of Neisseria gonorrhoeae Strains With Amino Acid Substitutions in the Zoliflodacin Target GyrB Using a Dynamic Hollow Fiber Infection Model - Jacobsson, Susanne; Golparian, Daniel; Oxelbark, Joakim; Franceschi, Francois; Brown, David; Louie, Arnold; Drusano, George; Unemo, Magnus (Frontiers in Pharmacology, 2022)
Novel antimicrobials for effective treatment of uncomplicated gonorrhea are essential, and the first-in-class, oral spiropyrimidinetrione DNA gyrase B inhibitor zoliflodacin appears promising. Using our newly developed Hollow Fiber Infection Model (HFIM), the pharmacodynamics of zoliflodacin was examined. A clinical zoliflodacin-susceptible N. gonorrhoeae strain, SE600/18 (harbouring a GyrB S467N amino acid substitution; MIC=0.25 mg/L), and SE600/18-D429N (zoliflodacin-resistant mutant with a second GyrB substitution, D429N, selected in the HFIM experiments; zoliflodacin MIC=2 mg/L), were examined. Dose-range experiments, simulating zoliflodacin single oral dose regimens of 0.5, 1, 2, 3, and 4 g, were performed for SE600/18. For SE600/18-D429N, dose-range experiments, simulating zoliflodacin single oral 2, 3, 4 and 6 g doses, and zoliflodacin oral dose-fractionation experiments with 4, 6, and 8 g administered as q12 h were performed. Both strains grew well in the untreated HFIM growth control arms and mostly maintained growth at 1010 to 1011 CFU/mL for 7 days. Zoliflodacin 3 and 4 g single dose oral regimens successfully eradicated SE600/18 and no growth was recovered during the 7-days experiments. However, the single oral 0.5, 1 and 2 g doses failed to eradicate SE600/18, and zoliflodacin-resistant populations with a GyrB D429N substitution were selected with all these doses. The zoliflodacin-resistant SE600/18-D429N mutant was not eradicated with any examined treatment regimen. However, this in vitro-selected zoliflodacin-resistant mutant was substantially less fit compared to the zoliflodacin-susceptible SE600/18 parent strain. In conclusion, the rare clinical gonococcal strains with GyrB S467N substitution are predisposed to develop zoliflodacin resistance and may require treatment with zoliflodacin ≥3 g. Future development may need to consider the inclusion of diagnostics directed at identifying strains resistant or predisposed to resistance development at a population level and to strengthen surveillance (phenotypically and genetically), and possibly also at the patient level to guide treatment.